Reconstruction Of Research Management In Indonesia - Hidayat, Taufik; Darmawati, Wuri (Inovasi Pembangunan : Jurnal Kelitbangan, 2019)
Research in Indonesia has lost focus or priority. The focus or priority in conducting this research is very important, especially with the limitations that it has. No wonder if the results of research that have been done so far have been largely useless and less desirable. So that policymakers also tend to search from the outside and that is certainly more in line with their needs. Thus, a reconstruction of research management in Indonesia is needed. The theories about synergy become the analitycal framework of this research. This study uses qualitative research methods with descriptive approach. After doing the research, it was concluded that: In research activities in Indonesia there were 2 (two) major problems, namely: a small budget and few researchers. Both of these problems can be overcome by synergizing various parties, in this case: the Central Statistics Agency, the National Development Planning Agency, the Ministry of Higher Education Research and Technology, the K / L R & D Institutions and the regions, and the local government.